The Relationship of Positive Emotions with the Cancer Patients Quality of Life in Halfway House - Ema Yuliani; Ah Yusuf; Ni Ketut Alit Armini (Jurnal Ilmu Keperawatan Jiwa, 2020)
The diagnosis and the treatment process of cancer causes a decrease in the quality of life of the patient. Positive emotions broaden thought-action repertoires and build a psychological, social, and physical resources which can affect the health status. The purpose of this study was to analyze the relationship of positive emotions with the quality of life of the patients in Rumah Singgah Pasien Surabaya. This study used a cross-sectional design. The sample consisted of 43 cancer patients who live in Rumah Singgah Pasien IZI Jatim and Rumah Singgah Sasana Marsudi Husada Consecutive Sampling. The independent variable in this study was positive emotions that were measured using the Modified Differential Emotions Scale (mDES) questionnaire with Cronbanch’s ɑ = 0,882 and the content validity is 0,041, while the dependent variable of this study was the quality of life of the cancer patients measured using the European Organization for the Research and Treatment of Cancer Quality of Life Questionnare C30 (EORTC QLQ -C30). The data analysis used the Spearman's test with p value <0.05. The result of this study indicates that positive emotions and quality of life have a direct relationship with weak strength (p = 0.040) and (r = 0.315). Most of respondents had high level of positive emotions and great quality of life. It can be concluded that the higher the level of positive emotional experience, the higher the cancer patients’ quality of life.